Research on Coal Acoustic Emission Characteristics and Damage Evolution During Cyclic Loading - Zhili, Su; Shengguo, Jing; Wenbing, Xie; Qingteng, Tang (Frontiers in Earth Science, 2022)
The acoustic emission, energy, and damage evolution of coal samples for three kinds of uniaxial cyclic loading and unloading are deeply analyzed in this study. The evolution of total absorption energy, elastic strain energy, and dissipated energy of coal samples is related to the stress path, and the increasing amplitudes cycle loading has an obvious damage effect on coal samples. During the loading stage, the acoustic emission phenomenon is most active when loading is increasing and the Felicity and post-Kaiser phenomena appear. The acoustic emission phenomenon during constant loading does not obviously change, but rather becomes active with the increase of the equivalent load. The damage to the coal sample shows nonlinear change increasing loading and unloading and shows linear change for other stress paths. Compared to waveforms with stepwise increasing amplitudes cyclic loading, the failure process of the coal sample is more closely related to the size of the external load, which indicates that reasonable hydraulic design is beneficial to the stability of the confining pressure in the chamber of an underground pumped storage hydropower station.